(untitled) (International Journal of Engineering and Computer Science, 2015)
— Smartphones provides the facility adoption of various mobile applications. The goal of this project is to implement all in one mobile applications, and find out the intention of customers or users to use this application. In this paper, we explain our experiences on constructing speech recognition applications on smartphones. We are going to explain three different models of use for speech recognition systems on smartphones that are – speech recognition in the cloud, distributed speech recognition and embedded speech recognition; evaluating advantages and disadvantages of these models. Mobile Cloud Computing has improved the way of using the service by customer across the globe It integrates cloud into smartphone environment and overcome the drawbacks regarding to performance like battery usage, bandwidth and storage.